Dijital İkiz Araştırmalarında Sürdürülebilir Kalkınma Hedeflerinin Haritalandırılması: Düşük Kodlu Konu Modellemesi ve LLM Tabanlı Bir Değerlendirme Çerçevesi (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2026)
The adoption of the "2030 Agenda for Sustainable Development" by the United Nations General Assembly in 2015 established a global commitment to achieving the 17 Sustainable Development Goals (SDGs) by 2030. As the deadline approaches, science, technology, and innovation (STI) are considered vital in accelerating progress toward these goals. This study analyzes the relationship between 10,306 digital twin research publications indexed in the Web of Science (WoS) and the SDGs. Using topic modeling with the KNIME platform, hidden themes in the digital twin literature were identified and evaluated for their alignment with specific SDGs. Sub-goal relationships for each topic were established using new and the most popular models, locally via Ollama and remotely via OpenRouter. In addition, meso and micro-level analyses highlight the temporal evolution, thematic density, and research focus within digital twin technologies. The findings offer a detailed understanding of the intersection between digital twin technologies and sustainable development, providing strategic insights for developing future STI policies. The study also outlines key sustainability areas to focus on in digital twin research and provides researchers with an SDG-focused roadmap, creating a comprehensive framework for analyzing the impacts of technological innovations on sustainability.
Keywords: dijital ikiz; sürdürülebilir kalkınma hedefleri; inovasyon; bilim ve teknoloji politikası; yapay zeka